2014
DOI: 10.4304/jltr.5.5.1071-1084
|View full text |Cite
|
Sign up to set email alerts
|

A Sociolinguistic Investigation of Social Stratification and Linguistic Variation among the Kashmiri Speech Community

Abstract: Abstract-This paper is restricted to the investigation of linguistic variation among the Kashmiri speakers at the level of phonology and lexicon of their language in accordance with certain social variables, viz-a-viz. religion, education, region / socioeconomic status, age and occupation. In the present paper, an effort has been devoted to examine as to how the structure of the Kashmiri language varies at the level of phonology and lexicon, in accordance with above mentioned social variables. It also takes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
2
5
0
2
Order By: Relevance
“…As noted by Koka (2014), the speech of the literate and illiterate people exhibits remarkable variations in terms of the lexical items they use and the pronunciation of many words. In his study on phonological and lexical variation among the Kashmiri speakers, taking into account certain social variables such as religion, education, region/socioeconomic status, age and occupation, he found that literate people tend to use Standard-Kashmiri.…”
Section: Education-based Influence On the Use Of Loanwordsmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted by Koka (2014), the speech of the literate and illiterate people exhibits remarkable variations in terms of the lexical items they use and the pronunciation of many words. In his study on phonological and lexical variation among the Kashmiri speakers, taking into account certain social variables such as religion, education, region/socioeconomic status, age and occupation, he found that literate people tend to use Standard-Kashmiri.…”
Section: Education-based Influence On the Use Of Loanwordsmentioning
confidence: 99%
“…On the other hand, illiterate people use the non-standard Kashmiri because they do not have much contact with speakers of standard Kashmiri. Moreover, Koka (2014) states that the literate group tends to remain up to date with the latest advances in modern inventions. Hence, they borrow many lexical items from other languages like English.…”
Section: Education-based Influence On the Use Of Loanwordsmentioning
confidence: 99%
“…Thus, they are more likely to stay in contact with the speakers of standard Kashmiri. Conversely, Koka (2014Koka ( , p. 1076 observed that the illiterate group use the non-standard variety of Kashmiri in their daily conversation. Additionally, it has been noted that the speech of the literate and illiterate groups exhibit remarkable variations in terms of the lexical items they use (Koka, 2014(Koka, , p. 1081.…”
Section: Educational Levelmentioning
confidence: 99%
“…Conversely, Koka (2014Koka ( , p. 1076 observed that the illiterate group use the non-standard variety of Kashmiri in their daily conversation. Additionally, it has been noted that the speech of the literate and illiterate groups exhibit remarkable variations in terms of the lexical items they use (Koka, 2014(Koka, , p. 1081. Similar to the age group A1 whose ages ranged between 15-50 years, the speech of the literate group is characterised by scientific, modern and technical terminologies as opposed to that of the illiterate group.…”
Section: Educational Levelmentioning
confidence: 99%
See 1 more Smart Citation